Perception of community tolerance and prevalence of depression among transgender persons. Issue 1 (2nd January 2017) - Owen-Smith, Ashli A.; Sineath, Craig; Sanchez, Travis; Dea, Robin; Giammattei, Shawn; Gillespie, Theresa; Helms, Monica F.; Hunkeler, Enid M.; Quinn, Virginia P.; Roblin, Douglas; Slovis, Jennifer; Stephenson, Robert; et al.
ABSTRACT: The goal of the study was to examine the association between depression and perceived community tolerance after controlling for various demographic and personal characteristics, treatment receipt, and past experiences with abuse or discrimination. An online survey assessed depressive symptoms among transgender and gender nonconforming individuals. Depression was assessed using the 7-item Beck Depression Inventory for Primary Care (BDI-PC) and the 10-item Center for Epidemiologic Studies Depression (CESD-10) scale. The prevalence ratios (95% confidence intervals) comparing depression in persons who did and did not perceive their area as tolerant were 0.33 (0.20–0.54) for BD-PC and 0.66 (0.49–0.89) for CESD-10. Other factors associated with depression were experience with abuse or discrimination, lower education, and unfulfilled desire to receive hormonal therapy. Depression was common in this sample of transgender and gender nonconforming individuals and was strongly and consistently associated with participants' perceptions of community tolerance, even after adjusting for possible confounding. The association between desire to receive hormonal therapy and depression is a finding that warrants further exploration. Future research should also assess depression and changes in perception of community tolerance in transgender individuals before and after initiation of gender confirmation treatment.